Automated Detection and Surgical Planning for Focal Cortical Dysplasia with Multicenter Validation. Issue 5 (12th November 2022) - Mo, Jiajie; Zhang, Jianguo; Hu, Wenhan; Sang, Lin; Zheng, Zhong; Zhou, Wenjing; Wang, Haixiang; Zhu, Junming; Zhang, Chao; Wang, Xiu; Zhang, Kai
Abstract : BACKGROUND: In patients with surgically amenable focal cortical dysplasia (FCD), subtle neuroimaging representation and the risk of open surgery lead to gaps in surgical treatment and delays in surgery. OBJECTIVE: To construct an integrated platform that can accurately detect FCD and automatically establish trajectory planning for magnetic resonance–guided laser interstitial thermal therapy. METHODS: This multicenter study included retrospective patients to train the automated detection model, prospective patients for model evaluation, and an additional cohort for construction of the automated trajectory planning algorithm. For automated detection, we evaluated the performance and generalization of the conventional neural network in different multicenter cohorts. For automated trajectory planning, feasibility/noninferiority and safety score were calculated to evaluate the clinical value. RESULTS: Of the 260 patients screened for eligibility, 202 were finally included. Eighty-eight patients were selected for conventional neural network training, 88 for generalizability testing, and 26 for the establishment of an automated trajectory planning algorithm. The model trained using preprocessed and multimodal neuroimaging displayed the best performance in diagnosing FCD (figure of merit = 0.827 and accuracy range = 75.0%-91.7% across centers). None of the clinical variables had a significant effect on prediction performance. Moreover, the automated trajectory was feasible and noninferior to the manual trajectory ( χ 2 = 3.540, P = .060) and significantly safer (overall: test statistic = 30.423, P < .001). CONCLUSION: The integrated platform validated based on multicenter, prospective cohorts exhibited advantages of easy implementation, high performance, and generalizability, thereby indicating its potential in the diagnosis and minimally invasive treatment of FCD.